Prospective evaluation of spinal reflex excitability and perceived ankle instability following acute lateral ankle sprain in collegiate basketball players - Terada, M.; Taniyama, D.; Isaka, T. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background The retrospective studies have reported altered spinal reflex excitability of the lower leg muscles in patients with acute lateral ankle sprain (LAS); however, these authors relied on data without a pre-injury assessment. Prospective examination of the longitudinal changes in neural excitability from pre-injury characteristics would provide a more comprehensive view of the underlying neuromuscular impairments. This study aimed to prospectively examine spinal reflex excitability of the fibularis longus and perceived ankle instability following acute LAS in collegiate basketball players.